Aneurysms of Pancreaticoduodenal Artery due to Median Arcuate Ligament Syndrome, Treated by Open Surgery and Laparoscopic Surgery - Satoshi Tokuda; Shunsuke Sakuraba; Hajime Orita; Mutsumi Sakurada; Tomoyuki Kushida; Hiroshi Maekawa; Koichi Sato (Case Reports in Surgery)
Introduction. There are many possible causes of an abdominal visceral aneurysm, including the obstruction of the celiac artery by the median arcuate ligament (MAL). We report two cases of an aneurysm of the pancreaticoduodenal artery due to MAL syndrome that we treated surgically. Case Presentation. Case 1: a 66-year-old Japanese woman was diagnosed with a rupture of an aneurysm of the inferior pancreaticoduodenal artery. Because of the difficulty of endovascular therapy, we performed an emergency operation. We chose an abdominal operation, and the postoperative course was uneventful. Case 2: a 75-year-old Japanese man presented at our hospital with acute abdominal pain, nausea, and cold sweat. Our experience of treating MAL syndrome in case 1 enabled us to diagnose the disease accurately. We chose laparoscopic surgery, and the postoperative course was uneventful. Discussion. There are several treatment choices for an aneurysm of the pancreaticoduodenal artery due to MAL syndrome. We have performed only a release of the MAL for treatment, but it is difficult to conclude whether only releasing the MAL is enough to ensure a positive long-term prognosis. Regular follow-up is needed in such cases. Conclusion. Laparoscopic surgery can be considered one of the options for MAL syndrome.